New insights into genetic variant spectrum and genotype–phenotype correlations of Rubinstein‐Taybi syndrome in 39 CREBBP‐positive patients - Virginia Pérez‐Grijalba (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Rubinstein‐Taybi syndrome (RSTS) is a rare congenital disorder characterized by broad thumbs and halluces, intellectual disability, distinctive facial features, and growth retardation. Clinical manifestations of RSTS are varied and overlap with other syndromes’ phenotype, which makes clinical diagnosis challenging. CREBBP is the major causative gene (55%–60% of the cases), whereas pathogenic variants found in EP300 represent the molecular cause in 8% of RSTS patients. A wide range of CREBBP pathogenic variants have been reported so far, including point mutations (30%–50%) and large deletions (10%). Methods The aim of this study was to characterize the CREBBP genetic variant spectrum in 39 RSTS patients using Multiplex Ligation‐dependent Probe Amplification and DNA sequencing techniques (Sanger and Trio‐based whole‐exome sequencing). Results We identified 15 intragenic deletions/duplications, ranging from one exon to the entire gene. As a whole, 25 de novo point variants were detected: 4 missense, 12 nonsense, 5 frameshift, and 4 splicing pathogenic variants. Three of them were classified as of uncertain significance and one of the patients carried two different variants. Conclusion Seventeen of the 40 genetic variants detected were reported for the first time in this work contributing, thus, to expand the molecular knowledge of this complex disorder.